Presence of Three-Dimensional Sound Field Facilitates Listeners’ Mood, Felt Emotion, and Respiration Rate When Listening to Music - Ooishi, Yuuki; Kobayashi, Maori; Kashino, Makio; Ueno, Kanako (Frontiers in Psychology, 2021)
Many studies have investigated the effects of music listening from the viewpoint of music features such as tempo or key by measuring psychological or psychophysiological responses. In addition, technologies for three-dimensional sound field (3D-SF) reproduction and binaural recording have been developed to induce a realistic sensation of sound. However, it is still unclear whether music listened to in the presence of 3D-SF is more impressive than in the absence of it. We hypothesized that the presence of a 3D-SF when listening to music facilitates listeners’ moods, emotions for music, and physiological activities such as respiration rate. Here, we examined this hypothesis by evaluating differences between a reproduction condition with headphones (HD condition) and one with a 3D-SF reproduction system (3D-SF condition). We used a 3D-SF reproduction system based on the boundary surface control principle (BoSC system) to reproduce a sound field of music in the 3D-SF condition. Music in the 3D-SF condition was binaurally recorded through a dummy head in the BoSC reproduction room and reproduced with headphones in the HD condition. Therefore, music in the HD condition was auditorily as rich in information as that in the 3D-SF condition, but the 3D-sound field surrounding listeners was absent. We measured the respiration rate and heart rate of participants listening to acousmonium and pipe organ music. The participants rated their felt moods before and after they listened to music, and after they listened, they also rated their felt emotion. We found that the increase in respiration rate, the degree of decrease in well-being, and unpleasantness for both pieces in the 3D-SF condition were greater than in the HD condition. These results suggest that the presence of 3D-SF enhances changes in mood, felt emotion for music, and respiration rate when listening to music.